Pengaruh Korean Wave Dan Brand Ambassador Terhadap Keputusan Pembelian Melalui Citra Merek Pada Bukalapak - Abimanyu; Yoga Ramadhani Omar (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2023)
The purpose of this study is to determine the impact of the Korean Wave and Brand Ambassadors on Purchase Decisions at Bukalapak via Brand Image. The population in this study consists of all consumers aged 16 to >35 years who are aware that Son Jong Ki is a brand ambassador and that Son Jong Ki carries the influence of brand ambassadors and who have purchased at Bukalapak with a minimum of two purchases in the last four months. A sample of 160 people was obtained using the non-probability sampling technique with purposive sampling. Path Analysis is the statistical tool used. Statistical software is used to process data. According to the findings of this study, the Korean Wave has a positive effect on brand image, which is consistent with Brand Ambassador having a positive effect on brand image. Then, Brand Image has a positive effect on purchasing decisions, whereas Korean Wave and Brand Ambassador have no effect. For Korean Wave and Brand Ambassador, Brand Image becomes an intervening variable.